Supporting the business process lifecycle using standards-based tools closed loop BPM solutions. - Nainani, By Bhagat
Business processes integrate systems, partners and people to achieve key strategic and operations objectives. Examples of business processes include getting and filling orders, processing invoices, reconciling shipping notices and received goods and processing insurance claims and loan applications. The Holy Grail of enterprise computing is adaptive business processes that can be defined, refined and optimized to respond to changing business environments, government regulations and competitive pressures. This vision has followed us through the evolution of mainframes, Management Information Systems (MIS), packaged applications, J2EE-based application platforms, business process management systems (BPMS) are now, Service Oriented Architectures (SOA). We are getting there!